Preaching by the Book : Developing and Delivering Text-Driven Sermons. - Pace, R. Scott (Hobbs College Library., 2018)
Preaching by the Book is a practical handbook offering fundamental guidance for preachers beginning to explore their gifts, and fresh insights for seasoned veterans desiring to refine their craft.